Effect of Prophylactic Thoracic Duct Ligation in Reducing the Incidence of Postoperative Chylothorax during Esophagectomy: A Systematic Review and Meta-analysis - Lei, Yiyan; Feng, Yanfen; Zeng, Bo; Zhang, Xin; Chen, Jingfu; Zou, Jianyong; Su, Chunhua; Liu, Zhenguo; Luo, Honghe; Zhang, Shuishen (The Thoracic and Cardiovascular Surgeon, 2018)
Objectives There is no consensus on the effectiveness of prophylactic thoracic duct ligation (PLG) in esophagectomy for reducing the incidence of postoperative chylothorax. We performed a systemic review and meta-analysis to study its efficacy.Methods A systemic review of the publications was performed on three databases to identify all the relevant literature on comparative outcomes of PLG and nonprophylactic thoracic duct ligation (NPLG). The primary end point was the incidence of postoperative chylothorax.Results Seven studies with comparative data on PLG (n = 2,178) versus NPLG (n = 3,048) were identify from the current publications. Comparison showed no significant difference between PLG and NPLG on the incidence of postoperative chylothorax (relative risk = 0.431; 95% confidence interval, 0.186 to 1.002; p = 0.050).Conclusions Although some studies showed that PLG during the esophagectomy was effective to lower the incidence of postoperative chylothorax, no evidence was observed in the present meta-analysis. Further research is warranted to validate the findings.
Keywords: prophylactic thoracic duct ligation; chylothorax; esophagectomy; meta-analysis